Evidence for genetically determined degeneration of proprioceptive tracts in Friedreich ataxia. (9th July 2019) - Marty, Brice; Naeije, Gilles; Bourguignon, Mathieu; Wens, Vincent; Jousmäki, Veikko; Lynch, David R.; Gaetz, William; Goldman, Serge; Hari, Riitta; Pandolfo, Massimo; De Tiège, Xavier
Abstract : Objective: To assess with magnetoencephalography the developmental vs progressive character of the impairment of spinocortical proprioceptive pathways in Friedreich ataxia (FRDA). Methods: Neuromagnetic signals were recorded from 16 right-handed patients with FRDA (9 female patients, mean age 27 years, mean Scale for the Assessment and Rating Of ataxia [SARA] score 22.25) and matched healthy controls while they performed right finger movements either actively or passively. The coupling between movement kinematics (i.e., acceleration) and neuromagnetic signals was assessed by the use of coherence at sensor and source levels. Such coupling, that is, the corticokinematic coherence (CKC), specifically indexes proprioceptive afferent inputs to the contralateral primary sensorimotor (cSM1) cortex. Nonparametric permutations and Spearman rank correlation test were used for statistics. Results: In both groups of participants and movement conditions, significant coupling peaked at the cSM1 cortex. Coherence levels were 70% to 75% lower in patients with FRDA than in healthy controls in both movement conditions. In patients with FRDA, coherence levels correlated with genotype alteration (i.e., the size of GAA1 triplet expansion) and the age at symptom onset but not with disease duration or SARA score. Conclusion: This study provides electrophysiologic evidence demonstrating that proprioceptive impairment in FRDA is mostly genetically determined and scarcely progressive after symptom onset. It also positions CKC as a reliable, robust, specific marker of proprioceptive impairment in FRDA.